Recyclable Heterogeneous Palladium-Catalyzed Carbonylative Cyclization of 2-Iodoanilines with Aryl Iodides Leading to 2-Arylbenzoxazinones - Xu, Zhaotao; Huang, Bin; Zhou, Zebiao; Cai, Mingzhong (Synthesis, 2020)
A highly efficient and practical heterogeneous palladium-catalyzed carbonylative coupling of 2-iodoanilines with aryl iodides has been developed. The reaction occurs smoothly in toluene at 110 °C with N,N-diisopropylethylamine as base under carbon monoxide (5 bar) and offers a general and powerful tool for the construction of various valuable 2-arylbenzoxazinones with excellent atom-economy, high functional group tolerance, good to high yields, and easy recyclability of the palladium catalyst. The reaction is the first example of heterogeneous palladium-catalyzed carbonylative coupling for the preparation of diverse 2-arylbenzoxazinones from commercially easily available 2-iodoanilines and aryl iodides.
Keywords: palladium; benzoxazinone; carbonylative coupling; 2-iodoaniline; heterogeneous catalysis